The Muhi Quarry: A Fossil-Lagerstätte from the Mid-Cretaceous (Albian-Cenomanian) of Hidalgo, Central México - Cuevas, Victor Manuel Bravo; Rodríguez, Katia A. González; Rodríguez, Rocío Baños; Guerrero, Citlalli Hernández (IntechOpen, 2012)
None